Consumer Expenditures on Fresh Fruit and Vegetables - Florkowski, W.J.; Klepacka, A.M.; Nambiar, P.M.; Meng, T.; Fu, S.; Sheremenko, G.; Sarpong, D.B. (Postharvest Handling: A Systems Approach, 2014)
The majority of consumers across the globe do not eat the WHO daily recommended amount of fruits and vegetables. Actual consumption is influenced by a multitude of factors. This chapter focuses on household income and expenditure to illustrate the variation of fresh fruit and vegetable consumption using primary and secondary data from household surveys in Ghana, Poland, Republic of Korea and Uganda. Income importance is examined by tracking fresh produce expenditure by quantile or income category suggesting that low income households tend to limit fresh fruit purchases more than fresh vegetables. Households with the highest income disproportionately outspend all other households regardless of the country's economic development and present special postharvest requirements. Illustration of other socio-economic factors and their relevance to fresh produce consumption is provided. There are similarities in terms of the most frequent consumption of vegetables across countries, but there is variation in the frequency of fresh fruit consumption, opening opportunities for trade. © 2014 Elsevier Inc. All rights reserved.
Keywords: Consumption frequency; Daily recommended consumption; Education; Exotic fruit; Expenditure; Fruit vegetable consumption frequency; Ghana; Household; Poland; Regional differences; Republic of Korea; Rural consumer; Survey; Uganda; Urban consumer; Weekly expenditure